Retirement village physical activity and nutrition intervention process evaluation: Informing practice. (27th August 2018) - Jancey, Jonine; Holt, Anne‐Marie; Lee, Andy H; Kerr, Deborah A; Hart, Ellen; Robinson, Suzanne; Anderson, Annie S; Hills, Andrew P; Howat, Peter
Abstract : Objective: This process evaluation aimed to determine participants' perceptions of the strategies utilised in a six‐month intervention that set out to improve physical activity and nutrition in retirement village (RV) residents. Methods: Qualitative and quantitative data were collected from intervention participants residing in 17 RVs located in Perth, Western Australia, via self‐report questionnaires (n = 139) and semi‐structured interviews (n = 16). Results: Intervention resources were moderately useful and suitable. Program ambassadors were encouraging (86%), but more frequent, and more direct, contact were preferred. The main reason for withdrawing from the program was health‐related conditions (aches, pains, injuries). Conclusion: This study provides evidence that the intervention was reasonably appropriate for older adults residing in RVs. Program ambassadors were well accepted, a successful strategy that should be considered for future interventions in RVs. Increased face‐to‐face engagement was preferred, but such an approach will require greater investment. The findings contribute to a small research base concerned with health behaviour interventions in RVs.